A-16 The Clinical Utility of a Novel Dual-Task Assessment for Sport-Related Concussion in Collegiate Athletes. (18th June 2020) - Erdman, N K; Hertel, J; Saliba, S A; JM, MacKnight; Broshek, D K; Resch, J E
Abstract: Objective: To compare the clinical utility of a novel dual-task assessment for sport-related concussion (SRC) to other commonly-used clinical measures in collegiate athletes. Method: Participants consisted of 38 collegiate athletes (19 concussed and 19 matched comparisons, 53% male, age = 20.0 ± 1.34 years, height = 178.2 ± 12.12 cm, mass = 83.4 ± 21.89 kg). Participants were administered the dual-task assessment, Balance Error Scoring System (BESS), Standardized Assessment of Concussion (SAC), and tandem gait (TG) test within 48 hours (T1), at 5 days (T2), and when symptom-free (T3) following a diagnosed SRC. The novel dual-task assessment consisted of concurrent administration of the SAC and TG. The ImPACT and Sensory Organization Test (SOT) were administered at T3 in alignment with the university's concussion management policy. Sensitivity, specificity, and diagnostic accuracy using receiver operator curve analyses were calculated for each measure for T1-T3 using previously established interpretation guidelines. Results: For sensitivity, a range of values were observed from T1-T3 for the dual-task (88%–37%), BESS (47%–47%), SAC (53%–26%), TG test (53%–11%). Similarly, a range of specificity values were observed for the dual-task (58%–84%), BESS (84%–63%), SAC (79%–84%), and TG test (95%–100%) from T1-T3. At T3, the ImPACT and SOT were observed to have a sensitivity of 32% and 100% and specificity of 16% and 100%, respectively. A range of diagnostic accuracy values were observed from T1-T3 for the dual-task (84%–62%), BESS (59%–50%), SAC (64%–56%), TG test (82%–71%), ImPACT (T3 = 66%), and SOT (T3 = 50%). Conclusions: The dual-task assessment had comparable or higher diagnostic accuracy as other commonly-used clinical measures of SRC throughout clinical recovery in collegiate athletes.